Pupillary response to moving stimuli of different speeds - Yuexin Wang; Yining Guo; Jiajia Wang; Ziyuan Liu; Xuemin Li (Journal of Eye Movement Research, 2021)
Purpose: To investigate the pupillary response to moving stimuli of different speeds and the influence of different luminance environments.